Proteome responses of Gracilaria lemaneiformis exposed to lead stress. (October 2018) - Du, Hong; Liang, Honghao; Jiang, Yang; Qu, Xiaoxiao; Yan, Haibo; Liu, Xiaojuan
Abstract: Proteome response of plants is an important process that enables them to cope with environmental stress including metal stress. In this study, the proteome of Gracilaria lemaneiformis exposed to lead was investigated. Two-dimensional gel electrophoresis analysis revealed 123 protein spots, among which 14 proteins were significantly differentially expressed and identified using MALDI-TOF MS. Two of the up-regulated proteins were identified and predicted to be involved in photosynthesis and signal transduction, while eleven down-regulated proteins were functionally grouped into five classes including photosynthesis, energy metabolism, protein metabolism, carbohydrate transport and metabolism, and antioxidation proteins. There was also an up-regulation in superoxide dismutase, peroxidase, glutathione s-transferase, and heat-shock protein 70 upon Pb exposure. Proteomic studies provide a better picture of protein networks and metabolic pathways primarily involved in intracellular detoxification and defense mechanisms. Highlights: 14 proteins of G. lemaneiformis were differentially expressed under Pb pressure. Two up-regulated proteins were involved in photosynthesis and signal transduction. Eleven decreased proteins were related to energy, protein and carbon metabolisms. Antioxidation proteins and heat-shock protein 70 were increased. Proteomic studies provide a primarily picture of intracellular detoxification and defense mechanisms.